Hypertension and kidney disease Bluthochdruck und Nierenerkrankungen - Striepe, Kristina; Schmieder, Roland (Tägliche Praxis, 2020)
The association between kidney disease and hypertension is bidirectional and complex. The kidney could be actor and victim of arterial hypertension. Autoregulatory processes protect the kidney in subjects with mild to moderate arterial hypertension. Above a certain threshold autoregulatory processes fail and glomerular pressure increases, resulting in kidney damage. In contrast, renal disease could cause arterial hypertension via diverse mechanisms, for example increased activity of the sympathetic system, impaired vascular/endothelial function, extracellular sodium overload, extracellular volume overload, increased activity of the renin angiotensin system and vascular stiffening of large arteries. Since arterial hypertension is the most predominant factor for progression of chronic kidney failure, in subjects with arterial hypertension and kidney disease an office blood pressure value of 130-140/70-80 mmHg is advocated. In cases of overt proteinuria the recommended value is lower (systolic 120-130 mmHg). A blood pressure lower than 120/70 mmHg should be avoided because of an increasing cardiovascular mortality. Subjects with comorbid kidney disease and hypertension should be treated with a renin-angiotensin system inhibitor (RAS-inhibitor), this is recommended worldwide in several guidelines. The RAS-inhibitor should be combined with a diuretic or calcium antagonist or both. For patients with still uncontrolled hypertension, there is the option to get an interventional treatment, in particular renal denervation.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Blood pressure; Blood pressure targets; Kidney disease; Renal denervation; Renin-angiotensin system